First‐Principles Analysis of the Structural, Mechanical, Electronic, and Thermoelectric Behavior of XOsBi (X=$X=$ Nb, Ta, V) Half‐Heusler Compounds - Boutaiba, F.; Aidouni, Ahmed Amine; Ould‐Mohamed, Mounir; Belkharroubi, Fadila (physica status solidi (b), 2026)
We present a first‐principles study of the structural, mechanical, electronic, and thermoelectric properties of three previously unexplored half‐Heusler compounds: NbOsBi, TaOsBi, and VOsBi. The nonmagnetic ‐phase is found to be the most stable configuration for all three systems. Mechanical stability of the cubic structure is confirmed via Born–Huang criteria and phonon analysis. Electronic structure calculations show that NbOsBi and VOsBi are indirect semiconductors with HSE06+SOC band gaps of 1.09 and 0.95 eV, respectively, whereas TaOsBi exhibits metallic behavior at the Perdew–Burke–Ernzerhof level and semimetallic character under HSE06+SOC. Thermoelectric analysis indicates that NbOsBi and VOsBi achieve high Seebeck coefficients and low lattice thermal conductivity, resulting in figures of merit () of up to 0.742 and 0.730 at 900 K, respectively. These results suggest that these materials may act as potential candidates for thermoelectric applications.